EFEKTIVITAS AROMATERAPI LEMON TERHADAP TINGKAT EMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER I DI PUSKESMAS SEI ALAM KECAMATAN BENGKALIS KABUPATEN BENGKALIS PROVINSI RIAU - Rita, Nora; Lisviarose, Lisviarose; Nadia, Fatma; Novera Yenita, Riski (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
The discomfort felt by each pregnant woman is different in each trimester of pregnancy. One of the complaints that is often felt during pregnancy is emesis gravidarum. There are impacts caused by emesis gravidarum so treatment is needed to overcome them. Lemon Aromatherapy is a non-pharmacological therapy using the aroma of lemon which has a calming effect so that it can reduce the level of emesis gravidarum in pregnant women who inhale the aroma. The aim of the research was to determine the effectiveness of lemon aromatherapy on the level of emesis gravidarum in first trimester pregnant women at the Sei Alam Bengkalis Health Center, Bengkalis District, Bengkalis Regency, Riau Province. This type of quantitative research uses a pre-experimental design approach. This research was carried out at the Sei Bengkalis Community Health Center, Bengkalis District, Bengkalis Regency, Riau Province. The sample used in this research was 27 respondents. The sampling technique at the Sei Bengkalis Community Health Center was carried out using a purposive sampling technique. The results and discussion show that there is effectiveness of lemon aromatherapy in reducing the level of emesis gravidarum in pregnant women in the first trimester with p value = 0.000 which shows that there is the effectiveness of lemon aromatherapy in reducing the level of emesis gravidarum in pregnant women in the first trimester at the Sei Alam Bengkalis Community Health Center, Bengkalis District, Bengkalis Regency, Riau Province. With this research, it is hoped that health workers, especially at the Sei Alam Community Health Center, will be able to provide lemon aromatherapy to pregnant women in the first trimester so that the emesis gravidarum experienced by the mother is reduced and can be overcome.Keywords: Lemon Aromateraphy, emesis gravidarum.